THEORETICAL INVESTIGATION OF DIVALENT ION INSERTION INTO TUNNEL-TYPE MANGANESE DIOXIDE POLYMORPH - Lalu Suhaimi; Andy Tirta; Muhammad Hilmy Alfaruqi (Jurnal PPI Dunia, 2020)
Rechargeable battery plays an important role to support the implementation of clean and renewable energy. In this aspect, post Li-ion battery, such as Zn-ion battery is receiving great attention due to its low cost and enviromentally friendly. Therefore, studies of electrode materials for Zn-ion battery are of paramount importance. In this contribution, we present theoretical investigation to explore the potential use of tunnel-type manganese dioxide for zinc storage material. Our calculation suggests the stability of the material for Zn-ion battery application.